Brazing and soldering - Vaccari, John A.; Cook, Jerome T. (Fundamental manufacturing processes)
This program covers the array of common brazing and soldering methods, including: torch brazing, batch furnace brazing, continuous furnace brazing, dip brazing, induction brazing,iron soldering, and wave soldering. Joint design and preparation, brazable/solderable materials, brazing/ soldering filler metal types, and the types and uses of flux are also highlighted.